2014
DOI: 10.1124/dmd.114.058222
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Diosbulbin B In Vitro and In Vivo in Rats: Formation of Reactive Metabolites and Human Enzymes Involved

Abstract: Diosbulbin B (DB), a major constituent of the furano-norditerpenes in Dioscorea bulbifera Linn, exhibits potential antineoplasmic activity and hepatotoxicity. The metabolism and reactive metabolites of DB in vitro (with human and animal liver microsomes) and in vivo in rats were investigated. The human enzymes involved in DB metabolism were identified. DB was first catalyzed into reactive metabolites of 2-butene-1,4-dial derivatives dependent on NADPH and then trapped by Tris base or oxidized to hemiacetal lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Further study is to synthesize sufficient amounts of the chemical entity of emodin-GSH adduct that enables a dynamic quantification analysis to reflect the status and severity of injury. Notably, the emodin-GSH adduct was not detected in the plasma and urine, a similar observation was made in another research (Yang et al, 2014), this could be explained by the fact that the conjugated emodin was mainly excreted via bile (Bachmann and Schlatter, 1981) or the undetectable concentration of emodin-GSH adduct in blood or urine. On the basis of the detection of emodin-GSH adduct, the derivatization and detection of emodin-GSH conjugates or emodin-protein adducts in blood or urine deserve further investigation for clinical detection.…”
Section: Resultssupporting
confidence: 82%
“…Further study is to synthesize sufficient amounts of the chemical entity of emodin-GSH adduct that enables a dynamic quantification analysis to reflect the status and severity of injury. Notably, the emodin-GSH adduct was not detected in the plasma and urine, a similar observation was made in another research (Yang et al, 2014), this could be explained by the fact that the conjugated emodin was mainly excreted via bile (Bachmann and Schlatter, 1981) or the undetectable concentration of emodin-GSH adduct in blood or urine. On the basis of the detection of emodin-GSH adduct, the derivatization and detection of emodin-GSH conjugates or emodin-protein adducts in blood or urine deserve further investigation for clinical detection.…”
Section: Resultssupporting
confidence: 82%
“…Toxicological studies consistently showed that pretreatment with ketoconazole (KTC, inhibitor of P450 3A) protected the animals from hepatotoxicities and hepatic GSH depletion induced by DIOB. The chemically reactive cis -enedial intermediate was found to react with the sulfhydryl group of glutathione (GSH) and the primary amine group of N -acetyl lysine (NAL) to produce a chemically stable pyrrole derivative [ 21 , 22 , 23 ]. We hypothesized that the reactive metabolite generated in situ reacts covalently with cysteine (Cys) thiol and lysine (Lys) primary amines of hepatic proteins to generate covalent binding.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, diterpenoid lactones in DBT are found to be hepatotoxic. Actually, the parent diterpenoid lactones do not appear to be hepatotoxic, while the metabolic activation of the furan ring by cytochromes P450 (CYP450) is the key procedure of acute liver injury 25 , 41 – 43 . Considering low CYP expression in cell lines 44 , the in vivo animal experiments were therefore conducted to evaluate the potential hepatotoxicity of the DBT extracts.…”
Section: Discussionmentioning
confidence: 99%